Evaluation of Explicit Motor Timing Ability in Young Tennis Players - Bisio, Ambra; Faelli, Emanuela; Pelosin, Elisa; Carrara, Gloria; Ferrando, Vittoria; Avanzino, Laura; Ruggeri, Piero (Frontiers in Psychology, 2021)
A crucial ability for athletes playing sports that involve coincidence timing actions is motor timing ability. The efficiency of perceptual and motor processes underlying motor timing ability has been related to the motor experience gained in interceptive sports, such as tennis. In the present study motor timing ability in young tennis players (TP) and age-matched control participants (CTRL) was compared by means of a synchronization paradigm. Participants were asked to perform finger-opposition movements in synch to a metronome beating 0.5 Hz and 2 Hz in 1) a Bimanual coordination test, which compared the performance of the dominant hand with that of the contralateral hand, and 2) a Movement lateralization test, which compared the motor performance of the dominant hand during single-hand and bimanual tasks. Motor performance was evaluated through movement strategy (defined by touch duration -TD, inter-tapping interval-ITI and movement frequency) and movement accuracy (temporal accuracy defined by the synchronization error and spatial accuracy defined by the percentage of correct touches-%CORR_SEQ). Results showed that motor expertise significantly influences movement strategy in the Bimanual coordination test; tennis players’ TD was significantly higher than those of CTRL, specifically at 0.5 Hz. Furthermore, overall TP’s ITI values were lower than those of CTRL. Lastly, in the Movement lateralization test, the %CORR_SEQ executed with the right dominant hand by TP in the bimanual task was significantly higher than those of CTRL. A discussion about the role of motor expertise in timing ability and the related neurophysiological adaptations is provided.